Innovative design and comprehensive ergonomic assessment of an auxiliary colonoscopy handle device - Wang Ruigang; Li Haiyue; Liang Xiong; Wang Deyu; Zeng Qingyin; Wang Haoyu; Li Rui; Chen Kai; Wei Zhengjie; Zhang Xiaolu; Cui Qi; Jiang Xuan; et al. (Scientific Reports)
Abstract Colonoscopy is a critical tool for diagnosing and treating bowel diseases, yet it demands high physician skill and can lead to suboptimal patient experiences. Recent technological advancements have aimed to enhance colonoscopy procedures by improving ease of use and patient comfort. This study introduces a novel colonoscopy handle auxiliary device designed to reduce operator fatigue and improve work efficiency. The device was evaluated through surface electromyography (sEMG) to assess muscle engagement and a questionnaire to gauge subjective experiences. The results showed that the novel handle significantly reduced muscle load in several key muscle groups, particularly the left biceps brachii, left flexor carpi radialis, and left abductor pollicis brevis, without compromising the efficiency and quality of the colonoscopy procedure. Subjective feedback indicated that the novel handle was perceived as more comfortable and easier to operate, especially by novice users. The study suggests that the novel handle has the potential to alleviate occupational injuries among endoscopists and enhance the overall colonoscopy experience for both operators and patients. Further research is needed to refine the handle’s design and validate its clinical applicability.